Physiological telogen effluvium of the newborn/Band hypotrichotic nevus. - Cutrone, M.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2017)
In the first months the baby often presents in the occipital region a band hair loss; according to the popular tradition it is attributed to the clutch on the pillow during supine lying, although being really due to the last synchronous wave of hair loss occurring during the fetal life. Band hypotrichotic nevus is on the other hand a much rarer condition characterized by a longer persistence.